Collection Development In Libraries With Special Reference To Visually Challenged Users (Journal of Namibian Studies : History Politics Culture, 2023)
The study explores the collection development of university level printed and electronic information resources for persons with visually challenged in Braille libraries, as well as how these resources affect users with visual impairments in a manner similar to that of blind users.Persons with visually challenged desire access to pertinent material in the library in their preferred accessible format, just as blind persons can read newspapers, listen to CDs, or download electronic content from the Internet. The study comes to the conclusion that using collections, assistive technology, and ICT will enhance librarians' expertise and inclusive teaching. There must be a large growth in the number of books and materials that are accessible through commercial means if libraries are to serve those who cannot read print effectively or with an adequate library collection and services. All users, regardless of gender, age, ethnicity, political stance, or handicap, have a right to access knowledge, and libraries have an ethical obligation to provide that access. These individuals had a small range of Braille books to choose from up to this stage, but many institutions are now learning the significance it is to make products for blind and visually challenged users accessible. With the help of this study, university libraries will have the fundamental information they need to address challenges with the visually impaired access to print and electronic resources. People who were long disregarded can now access services that are both user-friendly and pertinent thanks to the usage of assistive technology and ICT. In the digital age, excellent library collections and services for the blind can be provided by organizations that serve people with impairments. The study further explores the challenges faced by users with visual impairments and their informational requirements, identifies unique library resources and services, and offers recommendations for enhancing library and information services for the visually impaired.